Turkish Society of Gastroenterology for United European Gastroenterology: A Mutual Relationship - J. Matthias Löhr; J. Matthias Löhr (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Matthias Löhr J. Turkish Society of Gastroenterology for United European Gastroenterology: A mutual relationship. Turk J Gastroenterol. 2024;35(4):264-265.